Synthesis of acyl oleanolic acid-uracil conjugates and their anti-tumor activity - Mo, Wei-bin (Chem Cent J, 2016)
BACKGROUND: Oleanolic acid, which can be isolated from many foods and medicinal plants, has been reported to possess diverse biological activities. It has been found that the acylation of the hydroxyl groups of the A-ring in the triterpene skeleton of oleanolic acid could be favorable for biological activities. The pyrimidinyl group has been constructed in many new compounds in various anti-tumor studies. RESULTS: Five acyl oleanolic acid-uracil conjugates were synthesized. Most of the IC(50) values of these conjugates were lower than 10.0 μM, and some of them were even under 0.1 μM. Cytotoxicity selectivity detection revealed that conjugate 4c exhibited low cytotoxicity towards the normal human liver cell line HL-7702. Further studies revealed that 4c clearly possessed apoptosis inducing effects, could arrest the Hep-G2 cell line in the G1 phase, induce late-stage apoptosis, and activate effector caspase-3/9 to trigger apoptosis. CONCLUSIONS: Conjugates of five different acyl OA derivatives with uracil were synthesized and identified as possessing high selectivity toward tumor cell lines. These conjugates could induce apoptosis in Hep-G2 cells by triggering caspase-3/9 activity. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13065-016-0217-5) contains supplementary material, which is available to authorized users.